Organizacija informacij na spletnih straneh biomedicinskih knjižnic Slovenije - Oven, Marjeta (Knjižnica, 2005)
A library home page should be a document providing information about library, its various services to and activities for the users. The purpose of the present research was an evaluation of the actual state of-the-art of library home pages of Slovene medical libraries, and a set of suggestions is offered for their improvement. The results of the research, based on the sample of medical libraries partaining to the Ljubljana medical circle, indicate that posibilities offered by databases accessible on internet are unutilizied. Medical libraries mostly use their web sites for presentation of their activities in a fairly rigid and unchanging format, including general information on the library, e-mail, mailing adresses, library regulations, but without much interactive information. The article indicates the necessity for improvement of the present state and offers a few advices on how to achieve the positive change.
Keywords: specialne knjižnice; medicinske knjižnice; internet; spletne strani